The Effects of Levosimendan on Microcirculation and Peripheral Perfusion in Septic Shock: A Pilot Study - Veronica Gagliardi; Francesco Ceccherelli; Antonello Lovato; Giuseppe Gagliardi (Life)
Septic patients can show multiorgan failure even after an apparent recovery of hemodynamic stability. The underlying mechanism is unclear, but the main pathological element is microcirculation impairment, leading to insufficient oxygen delivery. This study aimed to assess the effects of levosimendan administration on peripheral perfusion in the prodromic phases of sepsis and compare them with the variations in microcirculation perfusion occurring with conventional dobutamine therapy. Sixteen patients with sepsis were enrolled, eight of whom were treated with norepinephrine and levosimendan and the other eight with norepinephrine and dobutamine. We observed a trend of reduction in the hematic lactate concentration and an increase in peripheral perfusion in the patients treated with levosimendan. The latter also occurred in the dobutamine group, although to a lower degree. Hematic lactate was significantly reduced in the levosimendan group, probably because of the enhanced aerobic metabolism, due to both the action on mitochondrial KATP channels and the better oxygen delivery to cells. The lactate values varied from T0 (2.28 ± 0.25 mmol/L) to T2 (1.45 ± 0.31 mmol/L) in the levosimendan group vs. from T0 (2.79 ± 0.91 mmol/L) to T2 (2.92 ± 0.76 mmol/) L in the dobutamine group. Hence, levosimendan may be indicated in septic patients with impaired microcirculation and tissue oxygenation and, consequently, high lactate levels. Further studies are needed to draw a profile of levosimendan as a possible treatment to restore microcirculation in septic patients.